Inhibiting Factors of the Performance of Internal Government Supervisory Apparatus in Realizing Good Governance at the Regional Inspectorate of Mandailing Natal Regency - Surya, Irfan; Ritonga, Syafruddin; Batubara, Beby Masitho (Journal of Public Representative and Society Provision, 2025)
This study aims to analyze the inhibiting factors of the performance of the Government Internal Supervisory Apparatus (APIP) in realizing the principles of good governance in the Mandailing Natal Regency Inspectorate. Good governance is one of the main pillars in creating a transparent, accountable, and responsive government to the needs of the community. However, its implementation often faces various obstacles that affect the performance of APIP as an internal supervisor. This research method uses a qualitative approach with data collection techniques through in-depth interviews, observations, and document studies. The results of the study indicate that there are several main inhibiting factors, including: limited competent human resources, lack of budget support, weak independence of APIP in carrying out its duties, and resistance from the supervised organization. In addition, the low utilization of information technology in the supervision process is also a significant obstacle. This study concludes that to improve APIP performance in realizing good governance, it is necessary to strengthen human resource capacity through training, increase budget allocation, guarantee APIP independence, and optimize information technology. Strategic recommendations from this study are expected to be a reference for local governments in improving the internal supervision system in order to achieve better governance.